Marketing del “Taller Automotriz De Jonathan” de la ciudad de Babahoyo, periodo 2022. - Herrera Montezuma, Adriana Carolina (2023)
The realization of this case study that is based on the marketing of the "Jonathan Automotive Workshop" of the city of Babahoyo for the period 2022, which has been the object of analyzing the strategies that the company has with the purpose of Identify the problems that have arisen due to the inadequate management and application of marketing, since they are the fundamental part for the organization to position itself competitively in the Babahoyense commercial market. Therefore, the analysis approach has been fundamental, since there is a solid foundation on the factors that influence the marketing process and its strategies, thus allowing the basic aspects to be compared in the marketing process. marketing in order for Jonathan's Automotive Workshop to have more acceptance for the products and services it offers to both its current and potential customers, for which it was possible to show that there are gaps in the commercial procedures, promotion and innovation, which has meant that sales revenues have decreased in the business and that competition is the main beneficiary of these negative results.